Pengaruh Stres Kerja Dan Kepribadian Terhadap Produktivitas Kerja Pada Unit Keuangan Dan Norma Perempuan Di Kemenakertrans - Tungga Buana Irfana; Sonia Puji Prasiwi (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2022)
This study aims to determine the effect of work stress and personality on work productivity at KEMENAKERTRANS financial staff and female norms. The method of analysis used in this study is by multiple linier regression analysis method. Population used in this research is 200 employees KEMENAKERTRANS with sample 54 because only take at part of finance and part of woman norm, by using Random Sampling method. Data processing technique using partial test method (t-test) and simultaneous significant test (f-test). The results obtained in this study indicate that partially work stress and work productivity have no (negative), partially personality and work productivity have positive effect, and that work stress and personality simultaneously have positive and significant effect to work productivity.